ANALYSIS OF NEEDS FOR THE DEVELOPMENT OF ETHNOMATHEMATIC E-MODULES BASED ON RIAU MALAY CULTURE TO FACILITATE MATHEMATIC LITERATURE ABILITY OF SMA/MA STUDENTS - Damayanti, Nofita; Roza, Yenita; Maimunah, Maimunah (Universitas Tanjungpura, 2022)
This research aims to determine the needs of teachers and students before the formulation of Riau Malay based ethnomatematics e-module to facilitate student